An Investigation of the Basic Gymnastics Program in Preschool Children in Terms of Motor Development - Erol, Sadettin (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Achieving an adequate level of basic motor skills by the end of the preschool period is an important prerequisite for children's participation in many later sporting activities. However, only a few studies have focused on the assessment of motor competence before starting primary school in the population of preschool children in Turkey. Aim: The aim of this study is to present An Investigation of the Basic Gymnastics Program in Preschool Children in Terms of Motor Development Method: Preschool children with a body weight of 18.26 ± 2.48 kg and a mean height of 1.10±.03 cm, who participated in the basic gymnastics program (n=28), participated in the study voluntarily. In our study; (n:15) experimental group students 3 days 35 minutes on 8 weekdays. gymnastics program was applied for a period of time. The control group (n=13) students were not given any activity. In order to investigate the effects of the basic gymnastics program in terms of motor development; One-leg bounce, agility, ball catching, tennis ball throwing, 9m sprint, flexibility, vertical jump, standing long jump and hitting the target performance tests were performed at the beginning and end of the study. The effects of the tests were compared between the groups in the pre- and post-test order by performing repeated measurements of variance analysis (P < 0.05). Results: As a result of the analysis of the data, when the first and last measurements of the groups were compared, it was determined that the performance results of hop on one leg, agility, flexibility, vertical jump and standing long jump performance were better in the experimental group than the control group (P < 0.05). There was no statistically significant difference between the groups in the performance tests of catching the ball, throwing the tennis ball (9m), speed and hitting the target (P > 0.05). Conclusion: For 8 weeks, the basic gymnastics program led to positive differences in one-leg bounce, agility, flexibility, vertical jump and standing long jump performance.